Proposição de melhorias do processo de compras em departamentos acadêmicos da Universidade Federal de São Carlos através da gestão por processos - Ferro, Samira Cecilia Custodio (Universidade Federal de São Carlos, 2018)
The Purchasing Management plays an increasingly important role at the Federal University of São Carlos (UFSCar), once the responsible team, which also includes the Purchasing Department, works in an integrated way to enable the purchase of a wide variety of necessary items to meet the demands of both administrative areas and the three major pillars of the organization: teaching, research and extension, applied in all existing areas of knowledge at university. However, by being a complex organization, the procedures are changed constantly in order to attend random factors such as new legislation or new technologies leading to a great effort to adjust the government employee of the Academic Departments to this new reality. Thus, the main aim of the is to analyze and propose improvements (stated in the employees’ interview of the academic departments) that can be effectively applied to the UFSCar’s purchasing process. In order to reach this aim were used tools regarding the process management. A qualitative research was conducted by applying case studies as research method besides collecting data from sources as legislation, papers and books, interviews were carried out with selected employees to understand their routine and purchase method process in their respective areas. The areas for the research were chosen according to a non-proportional stratified sample of academic departments of the Center of Exact Sciences and Technology of the UFSCar. Through the mapping analysis of current status purchasing processes and its description, twelve possible improvements were identified among others like stock items management and “price registration minutes”. As a result, instruments and procedures with it consequent adjustments of the mapping macro process flowchart were created. The proposes resulted in, among which, a new future scenario, a practical guide to check the Federal Government Price Panel and suggestions regarding the new functionalities to Enterprise Resource Planning (ERP), which has been developed and used by UFSCar.
Proposal of improvement of the purchasing process in academic departments of the Federal University of São Carlos through process management
Keywords: Gestão por processos; Melhorias do processo; Gestão de compras; Process management; Process improvements; Purchase management; Gestíon de compras; Gestíon por proceso; Mejorías de proceso; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::PROCESSOS DE TRABALHO